DOI Komunikasi Pariwisata antara Pemerintah, Pengelola dan Masyarakat dalam Mengembangkan Potensi Wisata Berbasis Kearifan Lokal di Kabupaten Bengkulu Selatan - Valentino, Febrian Tomi; Narti, Sri; Murwani, Anis Endang Sri (Universitas Islam Balitar, 2025)
The development of local wisdom-based tourism in South Bengkulu through the Ayiak Manna Cultural Festival is still incomplete due to the lack of cooperation between the government, managers and the community. The research uses the Pentahelix model using qualitative descriptive methods based on observation, documentation and interviews. Academics were less involved in planning, the industrial sector did not collaborate enough with government, the arts community received limited guidance, and the media carried out limited promotion. Therefore, academics support research-based policies, industry promotes culture through innovations such as Sekundang batik, arts groups will preserve traditions, the government organizes festivals and the media increases visibility. Better collaboration is needed to support local cultural preservation and economic development. Further research is recommended using quantitative methods to measure the effectiveness of the Pentahelix model.